Recruitment of Child Soldiers in Nepal: An Analysis of Child Recruitment in the People's Liberation Army - Yazdani, Laili (Université Saint-Paul / Saint Paul University, 2015)
Based on children’s perceptions of recruitment, academic discourse often suggests that children voluntarily enlist in armed groups in Asia in response to political indoctrination. Using Nepal as a case study, secondary sources are analyzed to test the hypothesis that children do not voluntarily enlist in armed groups. Academic literature, official party documents, humanitarian and media reports are triangulated to contextualize agency in child recruitment in the People’s Liberation Army, the armed group of the Communist Party of Nepal-Maoist during the Maoist revolution between 1996-2006. Festinger’s (1957) theory of cognitive dissonance is used to analyze nonphysical elements of force involved in child recruitment. The research findings confirm the hypothesis and indicate that children assented to forced recruitment. Political indoctrination had little influence in coercing enlistment in comparison to other nonphysical elements of force. In attempt to improve psychosocial and socio-economic factors, particularly basic human needs exacerbated by conflict, enlistment was often coerced with rewards that positively influenced children’s perceptions of recruitment as voluntary. However, children’s perceptions of recruitment were negatively influenced when rewards were unfulfilled and when recruitment was coerced with threats.
Keywords: Nepal; Child Soldier; Recruitment; Agency; Force; Informed Consent; People's Liberation Army; Communist Party of Nepal-Maoist; Cognitive Dissonance Theory